UPAYA SEKOLAH EKSPOR DALAM MENCETAK EKSPORTIR BARU MELALUI PROGRAM STUDI INDEPENDEN BERSERTIFIKAT “BE A DIGITAL EXPORTER" - Ahmad Baheshti; Dira Ernawati (Jurnal Publikasi Manajemen Informatika, 2024)
The National Export School Foundation is an institution that provides export training by utilizing digital technology. The aim of this program is to train students in managing and developing their export business so that it can be competitive and sustainable by utilizing digital technology. In this program participants take part in routine activities consisting of providing material, preparing written work, and exams. Apart from that, there are activities such as seminars, export trips, and attending trade shows. The main activity in this program is the practice of developing an export business plan through empowering MSMEs. The author sees that the efforts made by the Export School can improve the country's export performance and realize the hopes initiated by the Indonesian Ministry of Trade to advance Indonesia's export activities by producing 500 thousand new exporters by 2030. The research method used uses a qualitative approach. Data collection was carried out using observation techniques and documentation of the results of observations that could be concluded. The results of this research are that students can carry out activities and develop products locally so they can be marketed globally. Through this activity, it is hoped that students will be able to carry out export activities.